2007
DOI: 10.1523/jneurosci.2588-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Improves Cerebellar Memory Formation by Activating Estrogen Receptor β

Abstract: Learning motor skills is critical for motor abilities such as driving a car or playing piano. The speed at which we learn those skills is subject to many factors. Yet, it is not known to what extent gonadal hormones can affect the achievement of accurate movements in time and space. Here we demonstrate via different lines of evidence that estradiol promotes plasticity in the cerebellar cortex underlying motor learning. First, we show that estradiol enhances induction of long-term potentiation at the parallel f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 60 publications
5
68
0
Order By: Relevance
“…4b, e) in all the conditions tested here. Yet, consistent with the notion that this form of PF-LTP is post-synaptically expressed and E2 exerts an effect at the post-synaptic level (Andreescu et al 2007;Coesmans et al 2004;LevRam et al 2002), we did not find any modification in the PPR in either the control condition or LTZ condition during PF-LTP (Fig. 4b, e).…”
Section: Neurosteroid E2 Regulates Ltp In Acute Cerebellar Slicessupporting
confidence: 92%
See 2 more Smart Citations
“…4b, e) in all the conditions tested here. Yet, consistent with the notion that this form of PF-LTP is post-synaptically expressed and E2 exerts an effect at the post-synaptic level (Andreescu et al 2007;Coesmans et al 2004;LevRam et al 2002), we did not find any modification in the PPR in either the control condition or LTZ condition during PF-LTP (Fig. 4b, e).…”
Section: Neurosteroid E2 Regulates Ltp In Acute Cerebellar Slicessupporting
confidence: 92%
“…The results presented here are also consistent with findings showing rapid effects of exogenous E2 as well as the influence of high circulating E2 levels on memory tasks and learning (Andreescu et al 2007;Leuner et al 2004). Indeed, in light of the data, the circulating and local E2 might interact to determine behavioral changes via multiple modes and time courses.…”
Section: Neurosteroid E2 Is Necessary For Vor Adaptationsupporting
confidence: 90%
See 1 more Smart Citation
“…Other in vivo studies demonstrated PF-PC synaptogenesis induced by learning a complex acrobatic motor skill (25) or PF-PC elimination by eyeblink conditioning (26). In the vestibular ocular reflex (VOR), which shares common output pathways with HOKR (1, 4), gaindecrease but not gain-increase adaptation was improved by estradiol treatment, which also increased PF-PC synapse density (27). In the present study, HOKR gain decrease during the recovery period was accompanied with the increase of synapse density.…”
Section: Discussionmentioning
confidence: 99%
“…Reelin binds to the very low-density lipoprotein receptor (VLDLR) and apolipoprotein E receptor 2 (ApoER2), both expressed by rodent and human PCs (Kim et al, 1996;Perez-Garcia et al, 2004). PCs of neonatal and adult rodents express aromatase (Biamonte et al, 2009), estrogen receptor b (Price and Handa, 2000;Jakab et al, 2001;Andreescu et al, 2007;Biamonte et al, 2009) as well as androgen receptor (Simerly et al, 1990). Estrogens promote the development and survival of PCs (Sakamoto et al, 2003) and PCs themselves are known to be a site of synthesis of estrogens (Tsutsui et al, 2000).…”
Section: Introductionmentioning
confidence: 99%